South-South trade agreements, location of production and inequality in Latin America - Alessia Lo Turco (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2005)
This study aims at evaluating the relation between South-South trade agreements, location of production and inequality in Latin Amer- ican RTAs. Following Sanguinetti et al.(2004) and Midelfart-Knarvik et al.(2000), an empirical model will be estimated to check whether industry localization was a®ected by the agreement. An ending sec- tion will then evaluate the overall impact of trade agreements on -convergence, i.e. the standard deviation of income levels of countries belonging to the same agreement.
Keywords: F02; F15; O14; O54; C33; 330